Simple Approach to Overcome Thickness Tolerance of Interlayer without Sacrificing the Performances of Polymer Solar Cells. Issue 18 (7th August 2019) - Jeong, Mijin; Jin, Ho Cheol; Moon, Doo Kyung; Kim, Joo Hyun
Abstract: Small‐molecule electrolyte (C6‐E‐OTs ) hybridized ZnO layer is provided as the electron transporting layer. The device based on the blend of PTB7 and PC71 BM as the active layer shows an enhanced power conversion efficiency (PCE) from 7.6% based on ZnO to 8.8% using theC6‐E‐OTs hybridized ZnO layer. The device can be further improved by simultaneously using aC6‐E‐OTs hybridized ZnO layer and a 5 nm thickC6‐E‐OTs as the interlayer. The synergy effect of hybridization and interlayer enhanced the PCE of the device to 8.9%, which is a 17.1% increase in comparison with the device based on ZnO. The presence ofC6‐E‐OTs hybridized ZnO and a 5 nm ofC6‐E‐OTs as the interlayer in the device with PTB7‐Th as the donor significantly improves the PCE from 8.0% based on ZnO to 9.4%, resulting in a 17.5% enhancement. Main contribution for enhancing the PCE of the device is the improved J sc, which results from the reduction of energy offset at the cathode interface. Thus, hybridized ZnO layer process can overcome the limitation faced by the thickness tolerance of interlayer. Abstract : Small‐molecule electrolyte (C6‐E‐OTs) hybridized ZnO layer is provided as the electron transporting layer. The device based on the blend of PTB7 and PC71 BM as the active layer shows an enhanced power conversion efficiency (PCE) from 7.6% based on ZnO to 8.8% using theC6‐E‐OTs hybridized ZnO layer. Hybridized ZnO layer process can overcome the limitation faced by the thickness tolerance of interlayer.